PKM PEMBERDAYAAN PROGRESIF SCIENCE AND INNOVATION DAN MANAJEMEN INTERNATIONAL COMPETITION BAGI SANTRI DAN GURU SMA PROGRESIF BUMI SHALAWAT - wahyu sabtiawan; Fida Rachmadiarti; Sifak Indana; Nadi Suprapto (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2022)
In 2021, Unesa PKM Team provided guidance to Bumi Shalawat Progressive High School teachers regarding making competition management and conducting trials on Bumi Shalawat Progressive High School students through internal competitions. Starting from the PKM application letter from the pesantren partner (the principal of SMA Bumi Shalawat) to Unesa, then follow-up activities were carried out and an activity was planned with the title, "PKM Progressive Science and Innovation Empowerment and International Competition Management for Students and Teachers of Bumi Shalawat Progressive High School " The outputs of PKM activities that have been achieved are websites for internal competitions at Bumi Shalawat Progressive High School, scientific articles to be published in national journals, publications in mass media, and videos of PKM activities uploaded on social media. Keywords: Progresif Science and Innovation, Internal Manajemen, Bumi Shalawat